Optical phonons in methylammonium lead halide perovskites and implications for charge transport - Sendner, Michael; Beck, Sebastian; Epding, Bernd; Kowalsky, Wolfgang; Pucci, Annemarie; Lovrinčić, Robert (Materials Horizons, 2016)
Lead-halide perovskites are promising materials for opto-electronic applications. Recent reports indicated that their mechanical and electronic properties are strongly affected by the lattice vibrations. Herein we report far-infrared spectroscopy measurements of CH3NH3Pb(I/Br/Cl)3 thin films and single crystals at room temperature and a detailed quantitative analysis of the spectra. We find strong broadening and anharmonicity of the lattice vibrations for all three halide perovskites, which indicates dynamic disorder of the lead-halide cage at room temperature. We determine the frequencies of the transversal and longitudinal optical phonons, and use them to calculate, via appropriate models, the static dielectric constants, polaron masses, electron-phonon coupling constants, and upper limits for the phonon-scattering limited charge carrier mobilities. Within the limitations of the model used, we can place an upper limit of 200 cm2 V−1 s−1 for the room temperature charge carrier mobility in MAPbI3 single crystals. Our findings are important for the basic understanding of charge transport processes and mechanical properties in metal halide perovskites.